The Enduring Legacy Structured Inequality in America's Public Schools - Ryan, Mark Edward (University of Michigan Press, 2020)
Enduring Legacy describes a multifaceted paradox-a constant struggle between those who espouse a message of hope and inclusion and others who systematically plan for exclusion. Structured inequality in the nation's schools is deeply connected to social stratification within American society. This paradox began in the eighteenth century and has proved an enduring legacy. Mark Ryan provides historical, political, and pedagogical contexts for teacher candidates-not only to comprehend the nature of racial segregation but, as future educators, to understand their own professional responsibilities, both in the community and in the school, to strive for an integrated classroom where all children have a chance to succeed. The goal of providing every child a world-class education is an ethical imperative, an inherent necessity for a functioning pluralistic democracy. The challenge is both great and growing, for teachers today will face an evermore segregated American classroom.